2021
DOI: 10.1016/j.cjco.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) Biomarker—Anti-DSG2—Is Absent in Athletes With Right Ventricular Enlargement

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This is in contrast with both studies by Chatterjee et al and Caforio et al, which found significantly more frequent and greater concentrations of autoantibodies in people affected with ARVC compared to healthy controls. A more recent study assessing healthy human athletes with physiologic right ventricular enlargement found that anti-desmoglein-2 antibodies were not present, indicating further that they may play pathologic role 22 . However, Caforio et al also assessed heathy relatives of people with ARVC and patients with noninflammatory and ischemic cardiac disease as well as healthy unrelated blood donors, finding that anti-heart and anti-intercalated disc antibodies were present in some of these patients, albeit at a lower frequency compared to patients with ARVC and affected relatives.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with both studies by Chatterjee et al and Caforio et al, which found significantly more frequent and greater concentrations of autoantibodies in people affected with ARVC compared to healthy controls. A more recent study assessing healthy human athletes with physiologic right ventricular enlargement found that anti-desmoglein-2 antibodies were not present, indicating further that they may play pathologic role 22 . However, Caforio et al also assessed heathy relatives of people with ARVC and patients with noninflammatory and ischemic cardiac disease as well as healthy unrelated blood donors, finding that anti-heart and anti-intercalated disc antibodies were present in some of these patients, albeit at a lower frequency compared to patients with ARVC and affected relatives.…”
Section: Discussionmentioning
confidence: 99%